Persistent and transitory shocks, learning, and investment dynamics - Huntley Schaller; Bartholomew Moore (Hamburg Institute of International Economics (HWWA), 1999)
This paper introduces a new approach to understanding investment. The distinctive feature of our approach is that shocks to the economic fundamentals have both persistent and transitory components, and that firms must disentangle the persistent from the transitory shocks. The model generates interesting dynamics. Simulations of the model show that the response of investment to changes in the interest rate can vary widely over time, that the current response of investment depends on the sequence of past shocks, that investment will respond less when the firm is confident about its beliefs and more when a change in economic fundamentals challenges the firm's beliefs, and that investment booms and crashes may occur without any change in the true state of the economy. Simulations of the model also show that it captures many “stylized facts“ of investment dynamics documented in previous empirical studies.
Additional information: Abstract only.
Keywords: E22; 330; Gesamtwirtschaftliche Investitionstheorie; Betriebswirtschaftliche Investitionstheorie; Schock; Realzins; Stochastischer Prozeß; Lernprozeß; Betriebliche Investitionspolitik; Anpassung; Theorie